2017
DOI: 10.1021/acs.jpcc.7b05259
|View full text |Cite
|
Sign up to set email alerts
|

Au(111)-Supported Pt Monolayer as the Most Active Electrocatalyst toward Hydrogen Oxidation and Evolution Reactions in Sulfuric Acid

Abstract: As a subnanometer thick platinum (Pt) film can have catalytic properties different from those of the Pt bulk, the research on the preparation and characterization of a Pt monolayer is fundamentally intriguing and may lead to cost-effective fuel cells. We devise an electroless deposition method to fabricate a Pt monolayer and use scanning tunneling microscopy (STM) to characterize its atomic structures. This method involves the use of carbon monoxide (CO) molecules as the reducing agent for PtCl 6 2− complexes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…On the other hand, how the electrocatalyst’s structure affects the HOR activity was analyzed by Liao et al [ 269 ], who evaluated the catalytic activity of a Pt monolayer deposited on an Au (111) substrate. Moreover, they found two relevant structures, well-defined hexagons (R-phase) and Moire structures (M-phase) ( Figure 20 ).…”
Section: Electrocatalysts and Electrodesmentioning
confidence: 99%
“…On the other hand, how the electrocatalyst’s structure affects the HOR activity was analyzed by Liao et al [ 269 ], who evaluated the catalytic activity of a Pt monolayer deposited on an Au (111) substrate. Moreover, they found two relevant structures, well-defined hexagons (R-phase) and Moire structures (M-phase) ( Figure 20 ).…”
Section: Electrocatalysts and Electrodesmentioning
confidence: 99%
“…Also, Liao et al. showed that Au(111) supported Pt monolayers had a higher activity towards hydrogen evolution and oxidation than Pt(111). The authors ascribed this behavior to a larger interatomic spacing in the Pt monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…The nanosheets exhibited better catalytic activity than the nanoparticles, in part because they had a larger surface area, and also because the of the closer contact between the nanosheets and the surface of the substrate, making the electronic transfer faster than with nanoparticles. Also, Liao et al [26] showed that Au(111) supported Pt monolayers had a higher activity towards hydrogen evolution and oxidation than Pt(111). The authors ascribed this behavior to a larger interatomic spacing in the Pt monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…Their deposits exhibit similar activity to the ones of this work, even though the deposition times used by them are two orders of magnitude longer. The larger activity of the electrodeposited Ni thin films may be explained by the work of Liao et al [38]. They found that the electrocatalytic activity of Au(111) supported Pt monolayer films towardss hydrogen oxidation and evolution was larger than the electrocatalytic activity of Pt(111).…”
Section: Synthesismentioning
confidence: 99%